2014
DOI: 10.3389/fgene.2014.00386
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cells as alternative human biomatrices for comet assay

Abstract: The comet assay is a valuable experimental tool aimed at mapping DNA damage in human cells in vivo for environmental and occupational monitoring, as well as for therapeutic purposes, such as storage prior to transplant, during tissue engineering, and in experimental ex vivo assays. Furthermore, due to its great versatility, the comet assay allows to explore the use of alternative cell types to assess DNA damage, such as epithelial cells. Epithelial cells, as specialized components of many organs, have the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 73 publications
(261 reference statements)
2
31
0
Order By: Relevance
“…On a positive note, with 1-10,000 cells it requires only extremely small cell numbers (Kelvey-Martin et al 1993). Up to now the comet assay has been successfully used, for example, to measure DNA damage and/or repair in leukocytes (Glei et al 2002b;Glei and Pool-Zobel 2006), buccal cells (Glei et al 2005), salivary gland tissue , primary colon cells (Glei et al 2006b), different cancer cell lines like HT29 (Munjal et al 2012), HT29 clone 19A (Glei et al 2002a(Glei et al , 2003, LT97 (Glei et al 2007), or HepG2 (Glei et al 2006a, and also different epithelial cells (Rojas et al 2014) like brain cells (Mohamed and Hussien 2016), sperm cells (Cortes-Gutierrez et al 2014), plant cells (Ventura et al 2013), yeast cells (Miloshev et al 2002), or Drosophila melanogaster (Gaivao and Sierra 2014). Meanwhile the comet assay has achieved a high degree of awareness.…”
Section: Methodical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…On a positive note, with 1-10,000 cells it requires only extremely small cell numbers (Kelvey-Martin et al 1993). Up to now the comet assay has been successfully used, for example, to measure DNA damage and/or repair in leukocytes (Glei et al 2002b;Glei and Pool-Zobel 2006), buccal cells (Glei et al 2005), salivary gland tissue , primary colon cells (Glei et al 2006b), different cancer cell lines like HT29 (Munjal et al 2012), HT29 clone 19A (Glei et al 2002a(Glei et al , 2003, LT97 (Glei et al 2007), or HepG2 (Glei et al 2006a, and also different epithelial cells (Rojas et al 2014) like brain cells (Mohamed and Hussien 2016), sperm cells (Cortes-Gutierrez et al 2014), plant cells (Ventura et al 2013), yeast cells (Miloshev et al 2002), or Drosophila melanogaster (Gaivao and Sierra 2014). Meanwhile the comet assay has achieved a high degree of awareness.…”
Section: Methodical Aspectsmentioning
confidence: 99%
“…Most of these investigations are based on the use of either whole blood or the fraction of leukocytes isolated by density gradient centrifugation. The use of epithelial cells is an exciting alternative for human biomonitoring studies assessing DNA damage as recently also reviewed (Rojas et al 2014). This report summarizes the so far widely accepted guidelines for the comet assay in different types of epithelial cells, with particular focus on lens cells, corneal cells, exfoliated tear duct cells, buccal cells, and nasal cells (including 3D mini organ cultures of human inferior turbinate epithelia).…”
Section: Clinical Applications and Biomonitoringmentioning
confidence: 99%
“…The guidelines for the correct use of the comet assay in genetic toxicology were launched at the International Workshop on Genotoxicity Test Procedures (IWGTP) and concluded that the alkaline version (pH > 13) is the best version of this assay for identifying genotoxic activity [31,36]. This comet assay can detect DNA single-strand breaks (SSB), alkali labile sites (ALS), DNA-DNA/DNA-protein cross-linking, and SSB associated with incomplete excision repair sites [36]. Figure 2 summarizes the endogenous and exogenous sources of DNA damage and the different approaches used in the comet assay for its detection.…”
Section: Comet Assaymentioning
confidence: 99%
“…Due to its versatility, this experimental test allows the exploration of the use of different cell types to assess DNA damage (e.g., epithelial cells). As most solid cancers have an epithelial origin, it becomes relevant to screen for the risk of DNA damage in these types of cells [36]. Epithelial cells are known to have common structural features but have diverse functions due to many specialized adaptations [36,[57][58][59].…”
Section: Ocular Cell Line Characteristics Refsmentioning
confidence: 99%
“…The study of genotoxic effects caused by xenobiotics allows the identification of hazards in environmental risk assessment [Valverde and Rojas, 2009]. Epithelial cells-specialized in many organs-have the potential to serve as biomatrixes for evaluating genotoxicity and, therefore, also as biomarkers of genotoxic effects [Rojas et al, 2014].…”
Section: Introductionmentioning
confidence: 99%